Melanotic Neuroectodermal Tumor of Infancy in the Ulna of an Infant: A Very Rare Tumor. Issue 1 (January 2021) - Kovoor, Cherry Cheriyan; Jayakumar, R.; Manjunath, Samarth
Abstract : Case: A 4-month-old boy presented with a nontender swelling of the right proximal forearm of 2 months' duration. Radiological evaluation showed lytic lesion surrounded by sclerotic bone in the ulna with soft-tissue extension. Histopathological examination showed tumor of round and epithelioid cells containing melanin, interpreted as melanotic neuroectodermal tumor. The patient underwent a wide excision of the shaft of the ulna with creation of radioulnar synostosis. There is no recurrence 6 years after surgery. Conclusion: Melanotic neuroectodermal tumor is rare in the appendicular skeleton and has to be differentiated from other round cell tumors and osteomyelitis. As far as we know, this is the first reported case in the ulna.